Penerapan 12 Prinsip Animasi Dan Motion Graphics Dalam Multimedia - Suyadi, Nadila Agnestesia; Zaki , Alfasyahri; Sitepu , Arjuna; Andrea , Kiki; Ikhwan, Ali (Jurnal Sains dan Teknologi (JSIT), 2023)
Multimedia is an amalgamation of several components, namely text, audio, animation and video with digital processes managed by computers. Animation is one of the components contained in multimedia, to convey information and as a means of entertainment. In animation, there are various kinds of images that are given commands so as to form movements or movements according to the specified duration so as to create the illusion of motion of the image. Along with the development of technology and scientific branches, the development of animation also has an impact. One of them is how the animation technique is presented so that it looks lively, interesting, and has a deep meaning so that it is easier for the audience to understand. This study aims as a case study to present the stages that can be done in order to create an interesting animation by adhering to the 12 principles of animation by Frank Thomas and Ollie Johnston Disney animators as well as the application of the motion graphic method, namely pieces of digital recording combined with the illusion of motion and images in animation using qualitative descriptive methods.